La virtualizzazione dei Musei alla prova del Covid-19: Un caso studio - Vilardo, Giulia; Mazali, Tatiana (Mediascapes journal, 2022)
The article explores how the Corona Virus pandemic has affected the cultural sector and the digital models adopted to address the forced closing of all museum institutions. By using as a case study the virtual tour implemented for the temporary exhibition "Invisible Archaeology" of the Egyptian Museum in Turin, Italy, the article analyzes data of generated traffic and how the general public is positively responding to the use of VR in museums. The results show that inserting digital assets in museums allowed the development of new types of art installations and gave space to new interpretations of the cultural and art sector.